Desenvolvimento de um sensor de umidade do solo biodegradável baseado em geometria do metamaterial do tipo CSRR para aplicações na agricultura de precisão - Silva, Lincoln Alexandre Paz (Universidade Federal Rural do Semi-Árido, 2021)
Precision agriculture aims to improve efficiency in agricultural activities through techniques for monitoring planting conditions. In this context, one of the monitored parameters is the soil moisture content, whose measurement indicates the volume of water present in a given volume of soil and allowing to direct irrigation activities to the field areas that need it most. As an alternative to commercial soil moisture sensors, there are devices based on complementary split-ring resonators, which are artificial planar metallic structures that can be classified as a type of metamaterial. Such resonators are sensitive to dielectric changes in the medium in which they are inserted and can be used as microwave sensors, given that it is possible to relate the variation of its frequency response with the parameter of a physical or chemical nature to be quantified. The objective of this work is to design and conceive a planar device based on the mentioned metamaterial topology, which can be used as a microwave sensor to estimate the soil moisture content. In order to minimize environmental impacts that may occur due to forgetfulness or damage to the device during its use, the material used as a dielectric substrate is polyacid lactic, a biodegradable thermoplastic commonly used in the construction of 3D printed objects. The results of simulation and experimental use of the sensor when subjected to hypothetical and real situations of moisture content variation in soils of different textures are presented. Finally, an autonomous monitoring system was developed and integrated with the device. The results obtained indicate the viability of the proposed sensor, given that it was possible to correlate the variation in the moisture content of the soil based on the displacement of device’s frequency response
Keywords: Monitoramento local; Sensor de micro-ondas; Sensibilidade dielétrica; Local monitoring; Microwave sensor; Dielectric sensitivity; ENGENHARIAS::ENGENHARIA ELETRICA